Estudio de factibilidad de un sistema recuperador de vapores COVs para terminales y estaciones de servicio Guayaquil. - López Vera, Edduard Marlon (2019)
The project presented is supported by research that is duly documented to support the feasibility of using vapor recovery units in stations at terminals and service stations in Guayaquil, with technical parameters and results already proven in gas recovery and ecological benefit. And economic that generates the use of these equipment of recovery uvrs. the project consists of two phases the information to know the process of dispatch of fuel and what causes this activity be in terminals or stations of service, and a study of economic feasibility by means of results already presented gives us a better perspective for future projects and better decision making.